Social Problems Guidelines : Paper Checklist (A) - Gibson, Greg (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Included in this research are the guidelines for grading the theory section of a Social Problems paper .Paper Objectives 1. To do sociology by applying a theoretical lens in the examination of a social problem. Theory selected for this assignment can be (1) structural functionalism, (2) value-conflict, or (3) social constructionism. Sources for these theories can be found in both required texts